Produksi dan Pemasaran Jagung di Kabupaten Maluku Barat Daya - Marlani Luanmasar; Natelda R. Timisela; Inta. P. N. Damanik (Jurnal Sosial Ekonomi Pertanian, 2022)
This study aims to formulate a strategy to increase corn production and marketing Sampling was done by simple random sampling using the Slovin formula with an error rate of 15 percent. The sample size is 30 farmers in West Oirata Village and 30 farmers in Nomaha Village. The sample of traders was taken using the tracing sampling method which in the end the large sample of traders was 2 people. Data analysis to answer the first objective is the Cobb-Douglass production function, the second objective is analyzed using margin share, and the third objective is analyzed using SWOT analysis. The results showed that the production factors that had a significant effect on corn production were land area and labor, while herbicides had an insignificant effect on corn production. The results of the analysis using margin share obtained two marketing channels for corn in the research area. The SWOT analysis shows that the most prioritized strategy for increasing corn production and marketing is improving the quality of human resources for corn farmers and Field Agricultural Officers (PPL). An efficient marketing channel is marketing channel I. The most prioritized strategy for efforts to increase production and marketing of corn is to improve the quality of human resources for corn farmers and agricultural extension workers through education, training and internships related to corn cultivation and postharvest processing.